2013
DOI: 10.1111/apt.12569
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: non‐invasive assessment of non‐alcoholic fatty liver disease – the role of transient elastography and plasma cytokeratin‐18 fragments

Abstract: Summary Background Non‐alcoholic fatty liver disease (NAFLD) affects 15–40% of the general population. Some patients have non‐alcoholic steatohepatitis (NASH) and progressive fibrosis, and would be candidates for monitoring and treatment. Aim To review current literature on the use of non‐invasive tests to assess the severity of NAFLD. Methods Systematic literature searching identified studies evaluating non‐invasive tests of NASH and fibrosis using liver biopsy as the reference standard. Meta‐analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
282
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(311 citation statements)
references
References 112 publications
10
282
1
10
Order By: Relevance
“…Overall, SSI performed best for the detection of significant fibrosis, advanced fibrosis and cirrhosis (AUROCs for SSI, FibroScan™ and ARFI were 0.86, 0.82 and 0.77 for diagnoses of ≥ F2; 0.89, 0.86 and 0.84 for ≥ F3; and 0.88, 0.87 and 0.84 for F4; respectively) [45••]. The results are similar to prior individual studies [39,55]. It appears that none of the three imaging methods could accurately predict < F2 fibrosis, so further optimization of ultrasound techniques is needed [45••].…”
Section: Comparison Of Liver Stiffness Measurement Techniquessupporting
confidence: 80%
See 2 more Smart Citations
“…Overall, SSI performed best for the detection of significant fibrosis, advanced fibrosis and cirrhosis (AUROCs for SSI, FibroScan™ and ARFI were 0.86, 0.82 and 0.77 for diagnoses of ≥ F2; 0.89, 0.86 and 0.84 for ≥ F3; and 0.88, 0.87 and 0.84 for F4; respectively) [45••]. The results are similar to prior individual studies [39,55]. It appears that none of the three imaging methods could accurately predict < F2 fibrosis, so further optimization of ultrasound techniques is needed [45••].…”
Section: Comparison Of Liver Stiffness Measurement Techniquessupporting
confidence: 80%
“…A recent meta-analysis of the use of TE in patients with NAFLD (9 studies, 1047 patients) suggests that TE has excellent diagnostic accuracy for cirrhosis (92% specificity and 92% sensitivity), good accuracy for F3 (82% specificity and 85% sensitivity), but modest accuracy for F2 (75% specificity, 79% sensitivity) [39]. Despite this, TE can rule out cirrhosis with a high NPV (~90%) [40].…”
Section: Radiographic Assessment Of Liver Stiffness As a Surrogate Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Considering serum biomarkers in NAFLD, either singly or in combination biomarkers may be a surrogate for the presence and degree of hepatic steatosis or steatohepatitis or may be associated with the presence and progression of liver fibrosis. 3,4 In their proof of concept study, Verna et al 5 identified that serum levels of Pentraxin-2 (PTX-2), a serum protein known to inhibit fibrosis in vitro, 6 appears to be significantly associated with both the presence and progression of NAFLD. Verna et al demonstrate a significant association between PTX-2 levels and the presence of NAFLD, with mean PTX-2 levels being significantly lower in patients with NAFLD compared with normal controls.…”
mentioning
confidence: 99%
“…36 The plasma cytokeratin levels are increased in patients with NASH compared to simple steatosis with 66% sensitivity and 82% specificity. 37 However it has limited utility as a single marker to identify NASH. The FIB-4 calculator estimates fibrosis using the patient's age, aminotransferase levels and platelet count.…”
Section: Non-invasive Methods For Assessment Of Severity and Monitorimentioning
confidence: 99%